Periodontal thermoresponsive, mucoadhesive dual antimicrobial loaded in-situ gel for the treatment of periodontal disease: Preparation, in-vitro characterization and antimicrobial study - Bansal, Monika (J Oral Biol Craniofac Res, 2018)
BACKGROUND: This study aimed to formulate and characterize in-situ gel containing levofloxacin and metronidazole to release drugs in controlled manner for treatment of periodontitis. MATERIAL AND METHODS: Medicated in-situ gel with levofloxacin (10% w/v), metronidazole (25% w/v) and vehicle in-situ gel without drugs having poloxamer 407 (20% w/v) and chitosan (0.5%, 1%, 1.5%, 2.0% 2.5% w/v) were prepared and characterized for physicochemical, mechanical properties, stability and in-vitro drug release. Fourier transform infrared spectroscopy and differential scanning calorimetery studies were done. Optimized formulation was evaluated by scanning electron microscope (SEM) and in-vitro antimicrobial activity against 5 bacterial strains. RESULTS: The results revealed that drugs and polymers were compatible to formulate. All formulations were light yellow, clear and syringeable except formulation having 2.5% w/v chitosan. pH was in the range of 6.20 to 6.74. 1.0% w/v and 1.5% w/v chitosan formulations showed gelation temperature 37 ± 0.32 °C and 34 ± 0.21 °C. Further, mucoadhesive strength indicated mucoadhesivity of gel. In-vitro release study of 1.5% w/v chitosan formulation showed initial burst where about 55–60% MZ and 60–70% LVF got released within 6–7 hrs followed by sustained release upto 48 hrs. SEM images of 1.5% w/v chitosan optimized medicated in-situ and vehicle in-situ gel appeared similar indicating homogeneous mixing of polymers with drugs. In-vitro antimicrobial study showed that medicated in-situ gel was more effective than vehicle. CONCLUSIONS: In conclusion, optimized 1.5% w/v chitosan in-situ gel was thermoresponsive, mucoadhesive, syringeable, and released drugs in slow and controlled manner with effectiveness against broad range of microbes.